Companion to public theology - Kim, Sebastian C. H. (Brill's Companions to Modern Theology, 2017)
Winner of the 2017 Choice Outstanding Academic Title Award Public theology has emerged in the twentieth and twenty-first centuries as theologians have increasingly entered the public square to engage complex issues. This Companion to Public Theology brings a much-needed resource to this relatively new field. The essays contained here bring a robust and relevant faith perspective to a wide range of issues as well as foundational biblical and theological perspectives which equip theologians to enter into public dialogue. Public theology has never been more needed in public discourse, whether local or global. In conversation across disciplines its contribution to the construction of just policies is apparent in this volume, as scholars examine the areas of political, social and economic spheres as well as issues of ethics and civil societies, and draw on contexts from six continents. Contributors are: Chris Baker, Andrew Bradstock, Luke Bretherton, Lisa Sowle Cahill, Letitia M. Campbell, Cláudio Carvalhaes, Katie Day, Frits de Lange, Jolyon Mitchell, Elaine Graham, Paul Hanson, Nico Koopman, Sebastian Kim, Esther McIntosh, Clive Pearson, Scott Paeth, Larry L. Rasmussen, Hilary Russell, Nicholas Sagovsky, Dirk J. Smit, William Storrar, David Tombs, Rudolf von Sinner, Jenny Anne Wright, and Yvonne Zimmerman.